Case Report: When Does Puberty Become Traumatic? - Tarazi-Sahab, Layla; El Husseini, Mayssa; Moro, Marie-Rose (Frontiers in Psychiatry, 2021)
Puberty provokes physiological upheaval that can be psychologically traumatic and destabilizing for the child. Before the transformations of puberty, the body is a protective vessel that acts as a stable reference for the child. A child's emotional security is derived from a sense of predictability and well-being. However, the nascent sexuality and burgeoning libido experienced during puberty can trigger unsettling changes in the psycho-affective and psycho-dynamic equilibrium of the child as he or she transforms into an adolescent. This article presents puberty as a transformative experience with traumatic impact that needs to be considered in therapy conducted with adolescents. At best, pubescent trauma can cause superficial issues in a child's adaptive abilities; at worse, it can lead to pathological symptoms. This article presents a qualitative study derived from a clinical case of an adolescent girl who expresses her pubescent suffering through social withdrawal and mutism. The study determines several symptomatic and traumatic indicators caused by the sudden physiological transformations of puberty, such as perceived breaches in a child's sense of safety and the child's ability to predict. The study also explores the feelings of helplessness, vulnerability, and aloneness that pubescent adolescents endure, which are then exacerbated by the sensed inability to turn to parents for help or peers for support.